Improvement of elementary science learning outcomes using guided experimentation method - Putri, Nur Lailia Swadika; Susanti, Romia Hari; Purnama, Martini Dwi (Education and Development Research, 2023)
This research aimed to increase students’ conceptual understanding of photosynthesis in science subject through the stages of initial experimentation, observation, hypothesis preparation, verification, and application of the concept in experimental methods. The researchers investigated how science learning on photosynthesis using experimental methods could improve student learning outcomes. This research employed a classroom action research as a type of research. The research design followed the Kemmis and Mc Taggart model that was composed of four stages in each cycle: planning, implementation, observation, and reflection. Data collection instruments included observation sheets, learning outcome tests, and documentation. The research began with the pre-cycle and followed by cycles I and II. The research findings showed that student learning outcomes could be improved through the use of experimental methods in photosynthesis and science subject. This was supported by an increase in percentage results from pre-cycle (18%), cycle I (56%), and cycle II (78%). Therefore, it could be concluded that the experimental method was able to improve the learning outcomes of grade IV students at SDN Gadang 1 Malang City in the science subject of photosynthesis.